Simulating Properties of “Seasonal” Variability in Solar Activity and Space Weather Impacts - Dikpati, Mausumi; McIntosh, Scott W.; Wing, Simon (Frontiers in Astronomy and Space Sciences, 2021)
Solar short-term, quasi-annual variability within a decadal sunspot-cycle has recently been observed to strongly correlate with major class solar flares, resulting into quasi-periodic space weather “seasons”. In search for the origin of this quasi-periodic enhanced activity bursts, significant researches are going on. In this article we show, by employing a 3D thin-shell shallow-water type model, that magnetically modified Rossby waves can interact with spot-producing toroidal fields and create certain quasi-periodic spatio-temporal patterns, which plausibly cause a season of enhanced solar activity followed by a relatively quiet period. This is analogous to the Earth's lower atmosphere, where Rossby waves and jet streams are produced and drive global terrestrial weather. Shallow-water models have been applied to study terrestrial Rossby waves, because their generation layer in the Earth’s lower atmospheric region has a much larger horizontal than vertical scale, one of the model-requirements. In the Sun, though Rossby waves can be generated at various locations, particularly favorable locations are the subadiabatic layers at/near the base of the convection zone where the horizontal scale of the fluid and disturbances in it can be much larger than the vertical scale. However, one important difference with respect to terrestrial waves is that solar Rossby waves are magnetically modified due to presence of strong magnetic fields in the Sun. We consider plausible magnetic field configurations at the base of the convection zone during different phases of the cycle and describe the properties of energetically active Rossby waves generated in our model. We also discuss their influence in causing short-term spatio-temporal variability in solar activity and how this variability could have space weather impacts. An example of a possible space weather impact on the Earth’s radiation belts is presented.